2021
DOI: 10.3389/fcimb.2021.700305
|View full text |Cite
|
Sign up to set email alerts
|

The Anti-Biofilm Efficacy of Caffeic Acid Phenethyl Ester (CAPE) In Vitro and a Murine Model of Oral Candidiasis

Abstract: Candida albicans is the main fungal species associated with the development of oral candidiasis. Currently, therapeutic options for these infections are limited by the adverse effects of antifungal drugs and by the emergence of drug resistant strains. Thus, the development of new antifungal agents is needed for the prevention and treatment of oral Candida infections. Caffeic acid phenethyl ester (CAPE) is a natural compound from propolis polyphenolic groups that exhibits many pharmacological properties. In thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 58 publications
5
19
0
Order By: Relevance
“…Furthermore, to the best of our knowledge, this is the first study that investigated the anti-C. albicans properties of EA using C. elegans. Our findings corroborate with previous studies using different invertebrate models, since the protective effect of EA on a Drosophila melanogaster model and the efficacy of CAPE on G. mellonella and C. elegans models have already been described against C. albicans [21,33,85]. EA had a protective effect on Drosophila melanogaster from infection with C. albicans SC5314.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Furthermore, to the best of our knowledge, this is the first study that investigated the anti-C. albicans properties of EA using C. elegans. Our findings corroborate with previous studies using different invertebrate models, since the protective effect of EA on a Drosophila melanogaster model and the efficacy of CAPE on G. mellonella and C. elegans models have already been described against C. albicans [21,33,85]. EA had a protective effect on Drosophila melanogaster from infection with C. albicans SC5314.…”
Section: Discussionsupporting
confidence: 92%
“…CAPE at 2× MIC (16 µg/mL) completely suppressed yeast-to-hyphal conversion without interfering with fungal growth. Microscopic images confirmed that CAPE inhibited hyphae formation, in agreement with other studies [85].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…However, few studies that have investigated the antifungal activity of CAPE as a single molecule or in combination with some antibiotics were found in the literature. De Barros and coworkers recently reported the ability of CAPE to inhibit the growth of both fluconazole-sensitive and fluconazole-resistant strains of C. albicans [ 23 ]. Moreover, Sun and coworkers found the synergistic effects of CAPE with caspofungin and fluconazole against C. albicans and fluconazole-resistant C. albicans , respectively [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%